2021
DOI: 10.1038/s41598-021-96274-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated bioinformatics analysis of differentially expressed genes and immune cell infiltration characteristics in Esophageal Squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is a life-threatening thoracic tumor with a poor prognosis. The role of molecular alterations and the immune microenvironment in ESCC development has not been fully elucidated. The present study aimed to elucidate key candidate genes and immune cell infiltration characteristics in ESCC by integrated bioinformatics analysis. Nine gene expression datasets from the Gene Expression Omnibus (GEO) database were analysed to identify robust differentially expressed genes (DEGs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 54 publications
3
18
0
Order By: Relevance
“…Our results demonstrated that a machine learning signature based on radiomics features extracted from GGOs on CT images is an accurate method to early differentiate COVID-19 pneumonia from other acute non-COVID-19 lung diseases. These results confirm the promising role of radiomics in the diagnosis of COVID-19 pneumonia and are in line with the most recent literature on this topic 21 24 . For example, Huang et al used radiomics to discriminate COVID-19 and influenza pneumonia by combining CT signs and quantitative features extracted from the initial unenhanced CT images 22 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results demonstrated that a machine learning signature based on radiomics features extracted from GGOs on CT images is an accurate method to early differentiate COVID-19 pneumonia from other acute non-COVID-19 lung diseases. These results confirm the promising role of radiomics in the diagnosis of COVID-19 pneumonia and are in line with the most recent literature on this topic 21 24 . For example, Huang et al used radiomics to discriminate COVID-19 and influenza pneumonia by combining CT signs and quantitative features extracted from the initial unenhanced CT images 22 .…”
Section: Discussionsupporting
confidence: 91%
“…For this reason, although the context of the current pandemic and the previous CT findings can be indicative of COVID-19 pneumonia, the differential diagnosis of GGOs remains a challenge 10 , 17 . Recently, a few studies outlined a growing interest toward imaging-based tools aimed to assist physicians in patient management 18 24 . Radiomics is one of these tools and it allows the extraction of large amounts of quantitative data from medical images 25 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They perform variety of biological analyses including immune responses based on the defined gene sets. Exploring abnormal immune cell infiltration is critical for developing novel transformative therapies to combat diseases such as cancer, myocarditis, and TB (11,12). Therefore, in order to characterize alterations in immune cell proportion landscape and transcriptomic profile, and to identify new molecular therapeutic targets, this study applied statistical and knowledgebased systemic investigations (such as semantic similarity, gene correlation, and graph theory parameters) to the blood transcription data of patients with TB.…”
Section: Introductionmentioning
confidence: 99%